2023
DOI: 10.3390/vaccines11081289
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Population-Based Studies Assessing Knowledge, Attitudes, Acceptance, and Hesitancy of Pregnant and Breastfeeding Women towards the COVID-19 Vaccine

Abstract: The anti-SARS-CoV-2 vaccination is recommended for pregnant women due to the high risk of complications. However, pregnancy has been associated with vaccine hesitancy. Our review aims at summarizing the existing literature about anti-SARS-CoV-2 vaccine hesitancy in pregnant and lactating women. The research was conducted on PubMed/MEDLINE, ExcerptaMedica Database (EMBASE), and Scopus, according to PRISMA guidelines. Articles regarding the COVID-19 vaccine’s acceptance and/or refusal by pregnant and lactating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Therefore, it has been stated that informing healthcare workers correctly about the vaccine and ensuring their vaccination is effective in controlling the pandemic can be of great importance. Especially nurses who are in one-to-one contact with patients should organize health trainings by their roles as educators and counselors to protect public health (45)(46)(47). The results obtained show that attitudes and hesitation toward COVID-19 vaccines may vary according to various situational factors.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it has been stated that informing healthcare workers correctly about the vaccine and ensuring their vaccination is effective in controlling the pandemic can be of great importance. Especially nurses who are in one-to-one contact with patients should organize health trainings by their roles as educators and counselors to protect public health (45)(46)(47). The results obtained show that attitudes and hesitation toward COVID-19 vaccines may vary according to various situational factors.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the absence of a clear motivation, it could be noticed that there is a prevalence of female patients in the first group that switch to a male prevalence in the second one. It is interesting to note that despite several studies in the literature trying to evaluate gender differences in COVID-19 vaccination acceptance or hesitancy, no one shows an age-specific break line [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after full-text assessment, three articles were removed due to aggre-gated data [16] and different comparison [17,18]. Because of the high heterogeneity of the remaining 64 records, we chose to present results separately for population-based studies (21 records included; previously published [19]) and results of hospital-based studies (43 records included [2,; reported in the current manuscript). The disagreement about reviewers during the selection process was around 10%.…”
Section: Literature Searchmentioning
confidence: 99%